2013
DOI: 10.1177/194008291300600103
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Concentrations of Two Highly Migratory Sharks (Prionace Glauca and Isurus Oxyrinchus) in the Southeastern Pacific Waters: Comments on Public Health and Conservation

Abstract: Despite the importance of sharks in structuring the marine food web, their biomass is declining dramatically throughout the world´s oceans due to fishing pressures. Sharks caught as by-catch in long-line fisheries are sold for shark fins in the Asian fish market and secondarily as trunk sales for local consumption and fish meal. In order to determine the levels of heavy metals (mercury and lead) in oceanic shark populations in South Pacific waters, analyses of 39 Prionace glauca and 69 Isurus oxyrinchus were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 42 publications
1
11
0
8
Order By: Relevance
“…Our comparison to the food standards had similar findings to Lopez et al, 2013: Hg concentrations in stomach, muscle and liver tissue samples from P. glauca and I. oxyrinchus did not exceed the limit proposed by Codex. However, it was mentioned that Hg levels may have been masked by another metal hence there could have been more Hg in the samples than what was detected (Ibid).…”
Section: Mercurysupporting
confidence: 85%
See 2 more Smart Citations
“…Our comparison to the food standards had similar findings to Lopez et al, 2013: Hg concentrations in stomach, muscle and liver tissue samples from P. glauca and I. oxyrinchus did not exceed the limit proposed by Codex. However, it was mentioned that Hg levels may have been masked by another metal hence there could have been more Hg in the samples than what was detected (Ibid).…”
Section: Mercurysupporting
confidence: 85%
“…Similarly, Lopez et al (2013) found that the mean Pb concentration in muscle, liver and stomach samples taken from blue sharks (Prionace glauca), and in muscle and liver samples from mako short fin sharks (Isurus oxyrinchus) exceeded this limit. Lopez et al (2013) concluded that their findings indicated a risk for human health from consumption of shark tissues by humans.…”
Section: Leadmentioning
confidence: 93%
See 1 more Smart Citation
“…López et al (2013) Tabla 2. Comparación con otros valores de mercurio hallados en músculo de otras especies de tiburones (valores en mg/kg en peso húmedo).…”
Section: Agradecimientosunclassified
“…2013, 2014bVannuccini 1999). Additionally, shark consumption is of great concern to human health because the meat contains high levels of heavy metals (lead and mercury) due to biomagnification (EscobarSánchez et al 2011;Lopez et al 2013;Pethybridge et al 2000). While the global shark fin trade has decreased since the 2000s, the shark meat (sharks and rays) trade increased by 42% from 2000 to 2011, with Brazil being a major importer of shark meat (Dent and Clarke 2015).…”
Section: Introductionmentioning
confidence: 99%